An Analysis of Students’ Difficulties in Translating Argumentative English Text by the Second Grade Students of Private High School - Regina Gresia F Nababan; Erika Sinambela; Donna Ria Pasaribu (Universitas Islam Negeri Palopo, 2025)
This study aims at analyzing the problems faced by students in translating argumentative texts from English to Indonesia, and the factors that contribute to those problems. A descriptive quantitative method was used in analysis data. A total population of 120 students in four classes and 29 a total sample who made up the student of Private High School comprised the population of this study. The results indicate that where only 12 or 4.13% of students got a score close to the maximum score, the students’ difficulties were found from questionnaire in the linguistic factor were 16 students (55%) and the non-linguistic factor 20 students (69%) and the students’ difficulties were found from interviewed in the linguistic factor were 18 students (62%) and the non-linguistic factor 20 students (69%). It was concluded that it was found that class XI students at SMAS PGRI 20 Siborong-borong experienced difficulties in translating argumentative texts which were more influenced by non-linguistic factors. Students’ difficulties in translating because they had never taken an English course was the most prominent factor that causes students to experience difficulties in translating texts with the highest percentage being 69%. Although the nonlinguistic factors were the most prominent factors that appeared the second-grade students of Private High School in translating argumentative text the linguistic factors also contributed in minor way to the difficulties in the translation that the students encountered especially dealing with difficulties in translating the long text, with the percentage was 62%.